ANALISIS YURIDIS TERHADAP PERJANJIAN PEMBIAYAAN KONSUMEN YANG TIDAK DIDAFTARKAN JAMINAN FIDUSIA (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Currently, many financial institutions (finance) and banks (commercial banks and credit) provide consumer financing (consumer finance), leasing (leasing), factoring (factoring). However, the facts on the ground show that there are often fiduciary recipients who do not register their Fiduciary Guarantee Deed with the Fiduciary Registration Office. Fiduciary guarantees that are not made with fiduciary guarantee certificates have complex and risky legal consequences. As a result of the Fiduciary Guarantee which is not made a fiduciary certificate or in authentic form before a Notary, the object of the Fiduciary Guarantee does not have the right of direct execution.This type of research can be classified in normative legal research, namely legal research conducted by researching library materials. This study examines the subject matter in accordance with the scope and identification of the problem through a statute approach carried out by examining the laws and regulations that relate to the legal issue under study. Data collection techniques used in the Normative Legal Research are library research methods which uses the library as a means of collecting data, by studying books as reference material related to the problems to be studied.The conclusion that can be obtained from the results of the study is that the legal consequences for institutions that do not have a notary deed and are not charged with fiduciary guarantees, the object of the fiduciary guarantee does not have the right of direct execution. Based on Law Number 42 of 1999, the legal consequence of not registering a fiduciary guarantee is that a fiduciary guarantee has not yet been born. So that the entire legal consequences attached to the fiduciary guarantee do not apply. Juridical analysis of consumer financing agreements that are not registered with fiduciary guarantees lead to complex and risky legal consequences, including fears of alleged non-tax state revenue evasion, lack of realization of the principle of publicity and no guarantee of legal certainty so that they do not have legal executive rights Fiduciary executions that are not registered can lead to conflict and allow one of the parties to file a lawsuit in court.Keywords: Financing Agreement, Unregistered, Fiduciary Guarantee